Managerial leadership and teaching performance in a language center in Tacna - Peru - Lara Cortez, Claudia Irene (2021)
The research has as main objective to determine the relationship between executive leadership and teaching performance at the Language Center of Jorge Basadre Grohmann National University – Tacna, 2019; where the research type is pure or basic, the level is correlational, and the design used is non-experimental, with a sample constituted by 50 teachers, where the technique is the survey, and the instrument is the questionnaire, on the other hand the approach is quantitative. It was found that 94% of teachers perceive the management leadership that characterizes the executives as regular, and the most distinguished dimension is to “Maintain order and rationality” therefore focusing on improving “the human and participative relationships” and 88% of teachers consider their teaching performance as high level, and the most distinguished dimension is the “Pedagogical skills” therefore focusing on improving the “Result of their pedagogical work”. It may be concluded that it does exist direct and moderate relationship between the executive leadership and the teaching performance, because it was obtained a value of Rho = 0,476 and a value of p= 0,000.